INTEGRATION OF BEHAVIORISTIC LEARNING THEORY AND LEARNING PRINCIPLES IN THE QUR'AN: A THEORETICAL REVIEW IN ENGLISH LANGUAGE LEARNING - anto, dariyanto; Iwan Satiri; Nabil (LPPM Sekolah Tinggi Ilmu Tarbiyah Al Marhalah Al Ulya Bekasi, Indonesia, 2025)
This article aims to examine the behaviorist learning theory integrated with the learning principles in the Qur'an for English language learning. This study uses is a library study method. The data are obtained through literature reviews from several resources such as books, Google scholar, DOAJ, Libgen.is, Elsevier. Relevant literature data are analyzed to review how behaviorist learning theory can be integrated with the learning principles of the Qur'an perspective in English language learning. The results of the study indicate that the integration of behaviorist learning theory with the learning principles in the Qur'an has strong relevance in the English language learning process, especially in forming positive behavior: patience, hard work, responsibility, and perseverance in seeking knowledge. This study is expected to contribute to a more holistic English language learning process and accommodate the fundamental learning principles in the holy the Qur'an.